FAKTOR-FAKTOR YANG MEMPENGARUHI CASH HOLDING PADA PERUSAHAAN MANUFAKTUR - Hollyana Hariputeri; Liana Susanto (Jurnal Paradigma Akuntansi, 2022)
The purpose of this study is to obtain empirical evidence regarding the effect of firm size, solvability, profitability, and growth opportunity on cash holding. This research was conducted using 76 data of manufacturing companies listed on the Indonesia Stock Exchange for the year 2016-2019 with a purposive sampling method of selection with predetermined criteria and processed using the e-views program 10. Based on the research conducted, the firm size and solvability have no significant effect on cash holding, profitability has a significant positif effect on cash holding, and growth opportunity has a significant negatif effect on cash holding. This research is expected to help management and investors to make decisions and make the best policies for the company, and add economics information, especially regarding cash holding and the factors that influence it.